BIOLEACHING OF COPPER SULPHIDE FLOTATION CONCENTRATE IN BATCH REACTION SYSTEM USING MESOPHILE AND THERMOPHILE MICROORGANISMS - RENATA DE BARROS LIMA (Dyna, 2012)
This work aims at optimizing the use of consortiaof mesophile and thermophile microorganisms (moderate and extreme ones) in the leaching process of copper sulphidesflotation concentrate, containing approximately 30% bornite (Cu5FeS4) and 70% chalcopyrite (CuFeS2), for extracting copper.The objective of the bioleaching tests was to evaluate the performance of those microorganisms, varying specific parameters such as: the composition of the leaching solution, the presence of an energy source (ferrous sulphate), and the inoculation of cultures . To ensure optimal conditions for the microorganisms to act, the pH, temperature, and stirring speed were controlled. Finally, from the microbial action and using agricultural fertiliser (N:P:K sources), a copper extraction of more than 85% was achieved.